Il Vate e il suo doppio ironico - Giani, Maurizio (Archivio d’Annunzio, 2020)
In Germany, beginning from the last decade of XIX century, the fame of Gabriele d’Annunzio grew increasingly thanks to a continue flow of translations, which made him one of the most celebrated writers of the Jahrhundertwende in the country of Goethe. Among the German admirers of the ‘Vate’ there were poets and novelists such as Stefan George, Hugo von Hofmannsthal and Heinrich Mann. On the contrary, Thomas Mann’s appreciation of d’Annunzio was problematic: he disliked his aestheticism, his superficial Nietzschean Übermensch cult and moreover his far too refined, turgidly baroque prose. Nevertheless, he read attentively his colleague’s narratives – albeit using German translations, unlikely George and his senior brother Heinrich –, and undoubtedly made allusions – often in a deeply ironical sense – to d’Annunzio’s Triumph of Death in his novel Tristan. This essay reconstructs the cultural context of the relation between Mann and d’Annunzio, and offers a detailed comparison of selected passages and/or fragments from both works aimed at analysing the nature of Mann’s borrowings from the Italian writer, in order to show the ‘dialectical’ character of such a procedure.